2006
DOI: 10.1017/s0030605306000391
|View full text |Cite
|
Sign up to set email alerts
|

Two remnant populations of the roofed turtle Kachuga trivittata in the upper Ayeyarwady River system, Myanmar

Abstract: The endemic roofed turtle Kachuga trivittata has been extirpated over most of its former range in the Ayeyarwady River system of Myanmar. Only two small remnant populations are known to survive. In a small stretch of the upper Chindwin River K. trivittata persists because local Shan villages traditionally ban the killing of large adult K. trivittata. The population has nevertheless declined dramatically during the last few years because of the erosion of the ban by migrant fishermen from central Myanmar who do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…; Kuchling et al. ). Two remnant wild populations were identified in the early‐2000s, one in the Chindwin River Basin (upper Chindwin River [Kuchling et al.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Kuchling et al. ). Two remnant wild populations were identified in the early‐2000s, one in the Chindwin River Basin (upper Chindwin River [Kuchling et al.…”
Section: Introductionmentioning
confidence: 97%
“…]) and the other in the Dokthawady River System (Kuchling et al. ). However, a subsequent survey in 2011 upstream from a newly constructed hydroelectric dam and impoundment showed that the only sandbanks where B. trivittata was known to nest had been inundated (Platt & Soe ); thus, wild individuals of the species were restricted to a population of <10 females (based on annual nesting effort) inhabiting a remote stretch of the upper Chindwin River in western Myanmar (Turtle Conservation Coalition ) (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the late 1960s, restocking programs are conducted for B. baska and C. borneoensis and similar efforts are currently attempted for H. thurjii , K. dhongoka , K. kachuga and K. trivittata (van Dijk et al . 2000; Kuchling et al . 2006; E. O. Moll, pers.…”
Section: Introductionmentioning
confidence: 99%